Indonesian Mangrove Sonneratia caseolaris Leaves Ethanol Extract Is a Potential Super Antioxidant and Anti Methicillin-Resistant Staphylococcus aureus Drug - Kholis Abdurachim Audah; Jufendi Ettin; Jason Darmadi; Norma Nur Azizah; Amalda Siti Anisa; Tedi Dwi Fauzi Hermawan; Conny Riana Tjampakasari; Rudi Heryanto; Intan Safinar Ismail; Irmanida Batubara (Molecules, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is an S. aureus strain that has developed resistance against ß-lactam antibiotics, resulting in a scarcity of a potent cure for treating Staphylococcus infections. In this study, the anti-MRSA and antioxidant activity of the Indonesian mangrove species Sonneratia caseolaris, Avicennia marina, Rhizophora mucronata, and Rhizophora apiculata were studied. Disk diffusion, DPPH, a brine shrimp lethality test, and total phenolic and flavonoid assays were conducted. Results showed that among the tested mangroves, ethanol solvent-based S. caseolaris leaves extract had the highest antioxidant and anti-MRSA activities. An antioxidant activity assay showed comparable activity when compared to ascorbic acid, with an IC50 value of 4.2499 ± 3.0506 ppm and 5.2456 ± 0.5937 ppm, respectively, classifying the extract as a super-antioxidant. Moreover, S. caseolaris leaves extract showed the highest content of strongly associated antioxidative and antibacterial polyphenols, with 12.4% consisting of nontoxic flavonoids with the minimum inhibitory concentration of the ethanol-based S. caseolaris leaves extract being approximately 5000 ppm. LC-MS/MS results showed that phenolic compounds such as azelaic acid and aspirin were found, as well as flavonoid glucosides such as isovitexin and quercitrin. This strongly suggested that these compounds greatly contributed to antibacterial and antioxidant activity. Further research is needed to elucidate the interaction of the main compounds in S. caseolaris leaves extract in order to confirm their potential either as single or two or more compounds that synergistically function as a nontoxic antioxidant and antibacterial against MRSA.